Growth and structure of ultrathin praseodymium oxide layers on ruthenium(0001). Issue 5 (9th November 2016) - Höcker, Jan; Krisponeit, Jon-Olaf; Cambeis, Julian; Zakharov, Alexei; Niu, Yuran; Wei, Gang; Colombi Ciacchi, Lucio; Falta, Jens; Schaefer, Andreas; Flege, Jan Ingo
Abstract : Unraveling in situ the nanoscale morphology, chemistry, and crystallographic structure of epitaxial praseodymia on a ruthenium single crystal support. Abstract : The growth, morphology, structure, and stoichiometry of ultrathin praseodymium oxide layers on Ru(0001) were studied using low-energy electron microscopy and diffraction, photoemission electron microscopy, atomic force microscopy, and X-ray photoelectron spectroscopy. At a growth temperature of 760 °C, the oxide is shown to form hexagonally close-packed (A-type) Pr2 O3 (0001) islands that are up to 3 nm high. Depending on the local substrate step density, the islands either adopt a triangular shape on sufficiently large terraces or acquire a trapezoidal shape with the long base aligned along the substrate steps.